Algeomitri analysis of location proposed dam Jernaf Sharqat / northern Iraq - Najim Abdula K. Al-Kraaey; Ahmed Jaffar A. Al-Jboury; Mohammed Kassim M. Al-Kaisy (Tikrit Journal of Pure Science, 2023)
To study the morphometric characteristics of importance in the geomorphological and hydrological studies, as is the study of a set of characteristics that can be measured through a set of mathematical models and processes based on digital elevation model (DEM) and the use of the program (ARCMAP), in order to determine the morphometric characteristics of characteristics of spatial, longitudinal, and formalism, The terrain of the basin of the valley Al-Jirnaf conducted some surveys of a section of the valley in Sharqat by adapting the mainstay of abandoned concrete, which is located at the downstream area of ​​the basin, and use it as a way station to measure innovative before the first Tumble rain for the year 2013-2014, it aims to achieve integrated data lend to achieve the project base strategically important to the region and supports investment and development in water resources management and how to keep them and use them aims to achieve integrated data lend to achieve important strategic project for the region and supports investment and development in water resources management and how to keep them and take advantage of the base, and the Cubs Giomitri analysis of the tank, which explains the form and extent of the reservoir of attributed to (158) meters above sea level to the alleged (173) meters above it sea level where the tank longitudinal form and punctuated by some bays and occasional longitudinal flowing in, and accounts areal and volumetric at all levels and their relationship with each other and interpretation of curves, that predispose database The dam is designed to give a picture of the islands that appear and the other by the sink when water levels change .